2012
DOI: 10.1111/j.1365-2362.2011.02635.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the value of apoB48 as a marker for atherosclerosis in clinical practice

Abstract: ApoB48 concentrations are highest in patients with FCH and in atherosclerotic subjects with T2DM. In patients not using statins, the surrogate atherosclerosis marker IMT correlates best with apoB48, suggesting that fasting apoB48 may help to detect subjects at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 43 publications
2
26
4
Order By: Relevance
“…Our findings may have implications on the pathophysiology of insulin resistance–sociated hyperlipidemia. This condition has been associated with increased intestinal TLRs secretion and is proposed to be a pathogenic factor for atherosclerosis . Hayashi et al found that intestinal SR‐BI levels were increased in mice and hamsters that developed insulin resistance, hyperinsulinemia, and hyperlipidemia in response to a high‐fat and a high‐fructose diet, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings may have implications on the pathophysiology of insulin resistance–sociated hyperlipidemia. This condition has been associated with increased intestinal TLRs secretion and is proposed to be a pathogenic factor for atherosclerosis . Hayashi et al found that intestinal SR‐BI levels were increased in mice and hamsters that developed insulin resistance, hyperinsulinemia, and hyperlipidemia in response to a high‐fat and a high‐fructose diet, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…These particles have been shown to be associated with impairment of endothelial function and asymptomatic peripheral arterial disease in patients with T2DM [16,17], and correlate with coronary artery disease and carotid intima-media thickness in subjects with normal serum TG levels [18,19]. The potential mechanisms by which lipoproteins such as apoB-48 play a role in the atherosclerotic process, besides mechanisms intrinsic to these particles such as inflammation may involve closely associated abnormalities in other lipoproteins such as HDL and LDL resulting in ‘atherogenic lipoprotein phenotype’ (low HDL and small dense LDL) [20,21]. …”
Section: Postprandial Dyslipidemia As a Risk Factormentioning
confidence: 99%
“…Alipour et al [144] reported postprandial accumulation of atherogenic remnants in patients with type 2 diabetes, familial combined hyperlipidemia (FCHL), familial hypercholesterolemia (FH), and CAD. ApoB-48 was highest in FCHL and atherosclerotic subjects with type 2 diabetes.…”
Section: The Value Of Apob-48 As a Marker For Atherosclerosis In Clinmentioning
confidence: 99%